THE APPLICATION OF FEATURE TECHNOLOGY IN DEVELOPING A CAD-BASED HIGH LEVEL PROCESS PLANNING SYSTEM - Ade Febransyah (Institute of Research and Community Outreach - Petra Christian University, 2005)
High-level process planning plays an important role in determining candidate process domains at the configuration design stage. Changing the process domains later increases the product development cycle and the product development cost. Therefore, determining the most appropriate manufacturing processes at the beginning stages of the design process becomes critical. However, high-level process planning systems have traditionally lacked integration of design synthesis and design evaluation. The objective of this paper is to propose a CAD-based high-level process planning system that will help designers decide whether or not the designs are worth pursuing. A hybrid approach incorporating design by feature and feature recognition approaches is proposed and implemented. Synergizing both advantages of both approaches will reduce the complexity of feature recognition algorithm without sacrificing the flexibility in creating a part model.